Transforming the EFL pedagogical approach towards digital age through online communities of practice (CoPs) - Norizan Abdul Razak; Murad Abdu Saeed (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Since most conventional classroom learning in which English is a Foreign Language (EFL) is still characterized by learners‟ traditional roles and lacks such dynamic collaboration and interaction, EFL learners are increasingly using Social Network Sites (SNSs) as online Communities of Practice (CoPs) in adopting collaborative learning and transforming the EFL pedagogical approach as a new strategy towards achieving success in the modern digital age. Based on the theoretical background of CoPs, the current study aims to investigate the application of SNSs as a CoP in providing EFL students with the opportunity to use English, and to improve their learning through collaborative interaction in the language. The subjects of this study were 24 active and regular members of the Only for English Learning Facebook (FB) Community– a group developed and maintained by the researchers – for EFL learners coming from different countries. As to gain further information and understanding from the participants of how such EFL learning practice could be improved, online questionnaire, semi-structure interview and commentary exchanges of interaction posts were used for data collection and analysis. The findings proved that such online CoPwas perceived as an effective learning environment conducive to promoting the EFL learners‟ writing, grammar, reading andpersonal and socio- cultural skills and domains. Their perception of this CoP significantly increased during the period of collaborative learning.